ADOLESCENTS’ SUBJECTIVE WELL-BEING FOLLOWING KNEE INJURY: A LONGITUDINAL STUDY ON PERCEIVED AUTONOMY SUPPORT - Khadidja Chougui; Mireille Joussemet; Emilie Lemelin; Jessica Collins; Dominique Audet; Geneviève A. Mageau; Thierry Pauyo (International Journal of Child, Youth & Family Studies)
During adolescence, knee injuries are common and can greatly affect patients’ subjective well-being. Social support has been identified as a buffer against ill-being after knee injury. Self-determination theory holds that optimal social support nurtures the psychological need for autonomy, which is defined as a sense of personal endorsement of one’s actions. This longitudinal study aimed to examine the contributions of perceived parent and physician autonomy support to the subjective well-being of knee-injured adolescents. A total of 44 adolescent patients (Mage = 14.7 years) from a paediatric sports medicine clinic participated. In the waiting room (T0), data on perceived parental autonomy support, subjective well-being, athletic identity, and knee function were collected. After their appointment (T1), participants rated their perception of physician autonomy support. Participants later reported their subjective well-being monthly, for 3 months (T2–T4). Descriptive analyses revealed that perceived parental autonomy support was positively and often strongly correlated with subsequent subjective well-being. The positive association remained significant solely at T3 in regressions controlling for physician autonomy support, baseline subjective well-being, and other key confounders. Perceived physician autonomy support was positively but non-significantly correlated with later subjective well-being. These results suggest that perceived autonomy support, particularly from parents, may help overcome the deleterious effects of knee injury on adolescents’ subjective well-being.